Education Actions Project: An experience of interaction and integration with community - Dell Antônio Guimarães, Gabriela; Albane, Sibele; Costa dos Santos, Pedro Henrique; Dell’Antonio Souza, Aline; de Almeida Siqueira, Angela; Batista Portugal, Flávia; Mechelli de Siqueira, Marluce (Guará Journal, 2018)
The Educational Actions Project aims to do health promotion and prevention of diseases associated with drugs consumption, as well spread knowledge about psychoactive drugs and healthy life habits. The Project is a set characterized by interative and integrative actions of guidance, health promotion and prevention ofharms related to Mental Health, Alcohol and Other Drugs, directed to UFES internal and external communities. The technical team counts with health students and of related areas, as well with voluntary professionals, linked to Centro de Estudos e Pesquisassobre Álcool e outras Drogas, the CEPAD. The educational actions take place on Centro de Ciências da Saúde, Hospital Universitário CassianoAntônio de Moraes, in person, as well on other camp of UFES, electronically, directed to promote actions of health education, according to the Ministério da Saúde technical area of mental health, alcohol and other drugs calendar. The Project is relevant to academical and capixaba communities, because stimulates protagonism of future health professional in actions of promotion and prevention, corroborating with the specialized literatureabout the importance of primary healthcare to the population.
Keywords: Health education; Prevention; Psychoactive substances